Pengaruh Metode Quantum Learning Terhadap Pembelajaran Bahasa Indonesia - Yunisa Oktavia; Zia Hisni Mubarak; Mhd. Johan (eScience Humanity Journal, 2026)
The purpose of this study is to describe the influence and interaction of the Quantum Learning method on the Indonesian language learning achievement of grade XII students of senior high school in Batam City. The research method applied is the experimental method. The population of this study is grade XII students of senior high school in Batam City. The sample of this study is grade XII students of SMA Negeri 1 Batam and SMA Negeri 5 Batam. The instrumentation that will be used in the study is a questionnaire and a test. From the results of the hypothesis test conducted, it shows that the combined variance of the two samples is 8.1. For the real level with ∝ = 0.05 and dk 30. The resulting t_hit is 3.746 and t_table = 1.661. It can be concluded that H_0 is rejected and H_1 is accepted because . This means that the learning outcomes of students who have high Indonesian language proficiency taught with the Quantum Learning method are higher than students who have high Indonesian language proficiency taught using conventional methods. The results of the data analysis carried out, can be described that F_hit for interaction, which is 0.16, while F_table with ∝= 0.05, namely F_0.05 (1;60)= 3.99. It can be concluded that H_0 is accepted and H_1 is rejected because . This means that there is no interaction between the quantum learning method and Indonesian language proficiency in influencing the learning outcomes of class XII students of SMA Negeri 1 Batam and SMA Negeri 5 Batam.